The effect of direct democratic institutions on income redistribution: evidence from Switzerland - Feld, Lars P.; Fischer, Justina A. V.; Kirchgässner, Gebhard (SSE EFI working paper series in economics and finance, 2007)
There is an intensive dispute in political economics about the impact of institutions on income redistribution. While the main focus is on comparison between different forms of representative democracy, the influence of direct democracy on redistribution has attracted much less attention. In this paper, employing both a composite index and measures of single institutions, we find that direct democracy is particularly associated with lower welfare spending. Moreover, we estimate a model which explains the determinants of achieved redistribution measured by Gini coefficients using panel data provided by the Swiss Federal Tax Office from 1981 to 1997. While our results indicate that less public funds are used to redistribute income and actual redistribution is lower, inequality is not reduced to a lesser extent in direct than in representative democracies for a given initial income distribution. -- Income Redistribution ; Direct Democracy ; Referendums ; Initiatives
Keywords: Arbeitspapier; Graue Literatur